Placing the Preferences of People with Profound Intellectual and Multiple Disabilities At the Center of End-of-Life Decision Making Through Storytelling. (December 2019) - Watson, Joanne; Voss, Hille; Bloomer, Melissa J.
With a focus on the use of narrative approaches, this article is a commentary on decision-making support for people with profound intellectual and multiple disability (PIMD) at the end-of-life. Due to improved health care, people with PIMD are living longer lives than ever before. Therefore, they are increasingly facing decisions relating to end-of-life care and planning. Despite the increased attention that has been given to end-of-life planning, opportunities to have preferences responded to at the end-of-life are more likely afforded to people considered to have cognitive and decision-making capacity. Those supporting people with PIMD to plan for and make decisions about end-of-life care face several challenges. These challenges are rooted in difficulties with communication exchange between people with PIMD and their communication partners, leading to a widely held perception of decision-making incompetence for this population. In response to this challenge, this article draws on empirical research to discuss decision-making support within the context of palliative care and advance care planning, specifically for people with PIMD. It promotes decision-making support as an approach to assist supporters of people with PIMD to allow those people's expressions of preferences to be acknowledged and acted upon at the end-of-life. The use of narrative is presented and discussed as a tool for enabling this responsiveness, specifically within the context of end-of-life planning.